2016
DOI: 10.1111/pce.12799
|View full text |Cite
|
Sign up to set email alerts
|

Tomato plants increase their tolerance to low temperature in a chilling acclimation process entailing comprehensive transcriptional and metabolic adjustments

Abstract: Low temperature is a major environmental stress that seriously compromises plant development, distribution and productivity. Most crops are from tropical origin and, consequently, chilling sensitive. Interestingly, however, some tropical plants, are able to augment their chilling tolerance when previously exposed to suboptimal growth temperatures. Yet, the molecular and physiological mechanisms underlying this adaptive process, termed chilling acclimation, still remain practically unknown. Here, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…This was unexpected since the accumulation of flavonoids and anthocyanins involved in ROS scavenging is an important adjustment during cold acclimation (Ruelland et al, 2009; Schulz et al, 2016). Several genes encoding enzymes involved in flavonol and anthocyanin biosynthesis were up-regulated during cold treatment in tomato leaves together with numerous genes coding for enzymes with antioxidant activity, in agreement with increased anthocyanin levels (Barrero-Gil et al, 2016). Whereas no corresponding data are available for tomato roots, expression of genes encoding enzymes involved in secondary metabolism, especially phenylpropanoid and lignin biosynthesis, is increased in the roots of a cold-tolerant compared to a sensitive rice cultivar after a short-term cold stress (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This was unexpected since the accumulation of flavonoids and anthocyanins involved in ROS scavenging is an important adjustment during cold acclimation (Ruelland et al, 2009; Schulz et al, 2016). Several genes encoding enzymes involved in flavonol and anthocyanin biosynthesis were up-regulated during cold treatment in tomato leaves together with numerous genes coding for enzymes with antioxidant activity, in agreement with increased anthocyanin levels (Barrero-Gil et al, 2016). Whereas no corresponding data are available for tomato roots, expression of genes encoding enzymes involved in secondary metabolism, especially phenylpropanoid and lignin biosynthesis, is increased in the roots of a cold-tolerant compared to a sensitive rice cultivar after a short-term cold stress (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, analysis of DEG detected in leaves of ‘Moneymaker’ during an exposure to 10°C for 3 h indicated that transcription factor activity dominated the early response together with GO terms for stress response and hormone biosynthesis and signaling (Barrero-Gil et al, 2016). In addition, metabolism was adjusted by accumulation of compatible solutes, activation of antioxidants systems and rearrangement of the photosynthetic machinery (Barrero-Gil et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations